Immunotherapy in Testicular Germ Cell Tumors - Kalavska, Katarina; Schmidtova, Silvia; Chovanec, Michal; Mego, Michal (Frontiers in Oncology, 2020)
Testicular germ cell tumors (TGCTs) are malignancies with very high curative potential even in metastatic settings, mainly due to the introduction of cisplatin in the treatment of this disease. However, in a group of patients with cisplatin-refractory disease or with progressive disease despite high-dose salvage chemotherapy treatment, the prognosis is typically dismal. The triple combination of gemcitabine, oxaliplatin, and paclitaxel (GOP) has reasonable efficacy and is considered to be standard care for this group of patients. It remains to be seen, however, whether refractory TGCTs may represent a potential target for immune checkpoint inhibition. This review will focus on the rationale of the use of immunotherapy for platinum-refractory TGCTs and summarize data reporting experiences with immune checkpoint inhibitor treatment for this malignancy.